Determinants Of Financial Performance Of Digital Banks In The Indonesia Stock Exchange - Ima Kristina Yulita (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Financial transactions have become a necessity for almost everyone and organizations in the present day. The existence of digital banks utilizing financial technology for their operational activities greatly aids customers who seek fast, convenient, and time-saving transactions. This research aims to identify the factors influencing the financial performance of digital banks listed on the Indonesia Stock Exchange. Financial performance is measured by Return on Asset. The research sample consists of 6 digital banks listed on the Indonesia Stock Exchange, using data from 2016 to 2022. The data is analyzed using Multiple Linear Regression Analysis. The results show that Foreign Ownership, Capital Adequacy and Operating Costs to Operating Revenue have an impact on financial performance, while Institutional Ownership and Loan to Deposit Ratio do not affect the financial performance of digital banks. This implies that foreign ownership, Capital Adequacy, and Operating Costs to Operating Revenue factors should be a consideration for investors planning to invest in digital banks.